Commercial arbitration and the right to a fair trial: the relation that never worked out - Bassily, Ramy (AUC Knowledge Fountain, 2013)
Commercial Arbitration continues to be the most preferable dispute resolution mechanism for business owners and companies. That does not mean, however, that the mechanism is free of defects, as while the legislatures and scholars were working on enhancing the mechanism, they disregarded the basic principles of the rule of law. This thesis points to emphasize the imbalance between the advantages of the arbitration mechanism and the respect of the principles of law. It typifies the effects of this imbalance on the mechanism as a whole. It also suggests some solutions that do not diminish the advantages of the mechanism, but enhance congruence between the mechanism and the legal principles. The thesis, by focusing on a new problem that began to appear, aims to encourage legislatures and scholars to reconsider their liberal approaches with regard to arbitration rules amendments.